The effect of company size, profitability, and intangible assets on transfer pricing aggressiveness in energy sector companies listed on the Indonesia and Singapore stock exchange - Hadwimantoro, Hadwimantoro; Sari, Diana (WIM Solusi Prima, 2025)
This research investigates the impact of firm size, profitability, and intangible assets on the aggressiveness of transfer pricing in energy sector companies listed on the Indonesia Stock Exchange (IDX) and the Singapore Exchange (SGX). Employing a quantitative descriptive method, the study applies panel data regression analysis to examine the proposed hypotheses. A purposive sampling technique was used to select a sample of 13 energy companies listed on both the IDX and SGX during the 2017–2022 period. The data, spanning six years and comprising 78 observations, were sourced from the annual financial statements published by these companies. Analysis was conducted using eViews12 software. The results indicate that firm size negatively and significantly influences transfer pricing aggressiveness, with larger firms engaging less in aggressive transfer pricing. Meanwhile, profitability has no significant effect, suggesting that financial performance does not necessarily drive firms to engage in aggressive transfer pricing. Conversely, intangible assets positively and significantly impact transfer pricing aggressiveness, showing that firms with higher intangible assets tend to be more aggressive. This study provides empirical evidence on transfer pricing behavior in the energy sector under two different regulatory frameworks, offering insights for regulators and policymakers to monitor companies with substantial intangible assets.